Pengaruh Stres Kerja, Kepemimpinan Transformasonal dan kompensasi terhadap komitmen organisasi - Aprilia Ambarwati; Riska Fii Ahsani (LPPM Politeknik Pratama, 2025)
This research is a survey study conducted among 65 teachers of Muhammadiyah 1 Karanganyar High School, all of whom were used as research samples using a population research technique. Data were collected through questionnaires and literature studies. The data analysis techniques included multiple linear regression, t-test, F-test, and the coefficient of determination. The results showed that work stress had a significant negative effect on the organizational commitment of Muhammadiyah 1 Karanganyar High School teachers. Transformational leadership had a significant positive effect on organizational commitment, and compensation also had a significant positive effect on the organizational commitment of the teachers.